A Moral Analysis of Prostitution - Sotonye Big-ALobo (PT FORMOSA CENDEKIA GLOBAL, 2023)
The debate on the morality of prostitution has been a trending contemporary ethical issue. Some have argued for and some against prostitution. Prostitution, as I have defined it in the study, is the conscious act of any gender exchanging sex for financial or material gain. The study looked at the historical antecedents of prostitution, concepts and types of prostitution, and also brought forth various views or conceptions of prostitution. The views looked at include the feminist position for and against prostitution, the contractarian position for prostitution, and the liberalist and conservative positions on prostitution. The study adopted the qualitative method, and thus only secondary sources were used to carry out this research. The secondary sources used are from texts and journal articles. The study concludes that prostitution is neither coercive nor immoral if valid consent is obtained. Any sex act that takes place between two freely consenting adults is morally acceptable. Prostitution combines consenting sex with a contractual exchange. Hence, this dual aspect of the act serves as the foundation for any governing set of rules or morals that govern prostitution.